2003
DOI: 10.1074/jbc.m309833200
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Acid Sequence 442GDASE446 in Na/K-ATPase Is an Important Motif in Forming the High and Low Affinity ATP Binding Pockets

Abstract: .5 ) and the apparent K m for Mg 2؉ , Na ؉ , K ؉ , and vanadate in Na/K-ATPase were also estimated. For all the mutants, the value for ATP was ϳ2-10-fold larger than that of the wild type. While the turnover number for Na/K-ATPase activity were unaffected or reduced by 20ϳ50% in mutants G442(A/P) and D443A. Although both affinities for ATP effects were reduced as a result of the mutations, the ratio, K m l /K m h , for each mutant was 1.3ϳ3.7, indicating that these mutations had a greater impact on the low aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…It had been suggested that coupling to ATPase activity would exact an insupportable cost to cells for CFTR channel activity [26]. This present study confirms that CFTR possesses a very low specific activity (approximately three orders of magnitude lower than that of the Na + /K + -ATPase) [50]. Therefore it is unlikely that the ATPase activity of CFTR will be costly to the cell.…”
Section: Discussionsupporting
confidence: 76%
“…It had been suggested that coupling to ATPase activity would exact an insupportable cost to cells for CFTR channel activity [26]. This present study confirms that CFTR possesses a very low specific activity (approximately three orders of magnitude lower than that of the Na + /K + -ATPase) [50]. Therefore it is unlikely that the ATPase activity of CFTR will be costly to the cell.…”
Section: Discussionsupporting
confidence: 76%
“…This distortion in the V920E in the transmembrane segment might be related to the decrease in the affinity for Na ϩ and influence the conformational state of the N-domain such as to decrease the affinity for high affinity ATP effect and increase the affinity for low affinity ATP effects differently (Table I, e, f, and g). If these two apparent low affinity ATP effects structurally reflect the same single low affinity ATP binding conformation, the ratio K i,0.5 pNPPase /K 0.5 ATPase would be the same as the ratios in the data obtained from the mutagenesis of the ATP binding pocket as has already been reported (53,57). The ratio for the wild type and V920E was, respectively, 0.86 (0.43/0.50) and 0.42 (0.21/0.5).…”
Section: Fig 8 Atp Concentration Dependence Of Nak-atpase Activitysupporting
confidence: 54%
“…The relative turnover number was obtained by dividing rat Na,K-ATPase activity by the relative amount of EP max , estimated as described above. The value of the wild type was taken as 240 s Ϫ1 , which was estimated in a previous paper (57). To investigate the effect of ATP and K ϩ on Na,K-ATPase activity, 4 mM ATP and 16 mM K ϩ were replaced with 0 -4 mM ATP and 0 -16 mM K ϩ , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…1, D and E). Further structural analysis of the ND2 reveals that the N terminus of ND2 is highly exposed and does not contribute to ATP binding (30,31). Moreover, the corresponding domain in SR Ca 2ϩ -ATPase is known to bind phospholamban (32).…”
Section: Resultsmentioning
confidence: 99%